The Emergence of the Notion of Style in the Mentality of Old Russian Book Makers - Tsypkin, Denis O.; Simonova , Ekaterina S. (Actual Problems of Theory and History of Art, 2023)
The article completes a series of researches on the manuscript f. 115 No. 160 from the collection of Saint Petersburg Institute of History of the Russian Academy of Science. This manuscript, the so-called Stroganov ABC-book, was created in 1604 by the famous Moscow calligrapher Fyodor Basov for Nikita Stroganov. The paper presents important clarifications regarding the structure of the book. A careful analysis has revealed that the book was structured according to the category of style, which should be regarded as an important new notion in the mentality of professional Russian calligraphers of the time. The paper analyzes the Stroganov ABC-book in the context of definitions used in the 16th-17th century book inventories of Russian monasteries, where the similar notion of book ornaments has been also revealed. The concept of style can be found in such library inventories from the 1570s. Although some understanding of the stylistic peculiarities of book writing and decoration may have appeared only as a result of the so-called “second South-Slavic influence”, a clearer notion of style was probably formed by the adoption of Western types of decoration (the so-called Fryazhsky style) of Russian books and documents. The collision between the Byzantine (or Slavic-Byzantine) and Western traditions of book decoration obviously led to the shaping of the special category of style in the professional consciousness of the Muscovite calligraphers and scribes.The study was supported by the Russian Science Foundation, project no. 22-18-00615, in the National Library of Russia.
Keywords: style; Old Russian ornamentation; art of the book; Old Russian art; Old Russian manuscripts; inventories of monastery libraries; old-printed style